3D CT Evaluation of Common Crus Aplasia - Emmrich, J.V.; Fatterpekar, G.M.; Shlionsky, A.; Som, P.M. (American Journal of Neuroradiology, 2009)
SUMMARY: Aplasia of the common crus is an uncommon congenital anomaly. We present the case of a patient with common crus aplasia and discuss the relevant embryology and the role of 3D CT in evaluation of this rare congenital anomaly.